Challenges Faced by Second Language Learners in Writing Paragraphs at Secondary Schools: Teachers' Perspectives in South Africa - Lundi Nomlala (Studies in Learning and Teaching, 2026)
This paper investigates challenges South African secondary school second-language (L2) learners face in paragraph writing and identifies effective pedagogical solutions, as perceived by their teachers. Using a qualitative case study design, data were collected from 12 in-service English First Additional Language (EFAL) teachers from the public secondary schools in a selected district of the Eastern Cape, South Africa. Participant demographics included teachers with 3 to 18 years of teaching experience, representing rural-area school contexts. The research instruments comprised a semi-structured interview protocol (schedule) with questions aligned with the study’s objectives. Data analysis employed thematic analysis, following Braun and Clarke’s six-phase model, involving verbatim transcription, inductive coding, and iterative theme refinement to identify patterns related to writing challenges and pedagogical strategies. Findings reveal internal factors (limited linguistic competence, poor planning, low confidence) and external factors (time constraints, few writing opportunities) as key difficulties. Specific challenges include constructing topic sentences, ensuring cohesion and coherence, and applying grammar. Effective strategies identified include explicit instruction on paragraph structure, process-oriented approaches, blended learning tools, and formative feedback. The study concludes that improving L2 paragraph writing requires a shift from product-focused evaluation to a scaffolded, process-oriented, technology-enhanced approach.